Genetic basis of early‐onset, maturity‐onset diabetes of the young‐like diabetes in Japan and features of patients without mutations in the major MODY genes: Dominance of maternal inheritance. Issue 7 (1st July 2018) - Yorifuji, Tohru; Higuchi, Shinji; Kawakita, Rie; Hosokawa, Yuki; Aoyama, Takane; Murakami, Akiko; Kawae, Yoshiko; Hatake, Kazue; Nagasaka, Hironori; Tamagawa, Nobuyoshi
Abstract : Background: Causative mutations cannot be identified in the majority of Asian patients with suspected maturity‐onset diabetes of the young (MODY). Objectives: To elucidate the genetic basis of Japanese patients with MODY‐like diabetes and gain insight into the etiology of patients without mutations in the major MODY genes. Subjects: A total of 263 Japanese patients with early‐onset, non‐obese, MODY‐like diabetes mellitus referred to Osaka City General Hospital for diagnosis. Methods: Mutational analysis of the four major MODY genes ( GCK, HNF1A, HNF4A, HNF1B ) by Sanger sequencing. Mutation‐positive and mutation‐negative patients were further analyzed for clinical features. Results: Mutations were identified in 103 (39.2%) patients; 57 mutations in GCK ; 29, HNF1A ; 7, HNF4A ; and 10, HNF1B . Contrary to conventional diagnostic criteria, 18.4% of mutation‐positive patients did not have affected parents and 8.2% were in the overweight range (body mass index [BMI] >85th percentile). HOMA‐IR at diagnosis was elevated (>2) in 15 of 66 (22.7%) mutation‐positive patients. Compared with mutation‐positive patients, mutation‐negative patients were significantly older ( P  = 0.003), and had higher BMI percentile at diagnosis ( P  = 0.0006). Interestingly, maternal inheritance of diabetes was significantly more common in mutation‐negative patients ( P  = 0.0332) and these patients had significantly higher BMI percentile as compared with mutation‐negative patients with paternal inheritance ( P  = 0.0106). Conclusions: Contrary to the conventional diagnostic criteria, de novo diabetes, overweight, and insulin‐resistance are common in Japanese patients with mutation‐positive MODY. A significant fraction of mutation‐negative patients had features of early‐onset type 2 diabetes common in Japanese, and non‐Mendelian inheritance needs to be considered for these patients.